“Prepare Your Physical Health”: Psikoedukasi Membangun Kesiapan Fisik dan Kesehatan Jelang Pernikahan - Wahyuni, Lussy Dwiutami; Ariyani, Mira; Putri, Fildzah Rudyah; Izzati, Adzkia Zahra; Luthfiyah, Syifa Ananda (Universitas Negeri Jakarta, 2024)
Pasirtanjung Village is one of the villages in Tanjungsari District, Bogor Regency. The high gap between job seekers and the availability of job opportunities which has an impact on the income they earn is one of the problems in this village. Meanwhile, income is one of the factors that has an impact on a person's readiness to live married life. In addition, people in this village still have the opinion that someone must get married immediately, without paying attention to the individual's readiness, especially in terms of physical and health. For this reason, the Faculty of Psychology, Universitas Negeri Jakarta offers a solution by holding psychoeducation with the theme